Quantification of Platelet Contractile Movements during Thrombus Formation - Tunströmer, Kjersti; Faxälv, Lars; Boknäs, Niklas; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2018)
Imaging methods based on time-lapse microscopy are important tools for studying the dynamic events that shape thrombus formation upon vascular injury. However, there is a lack of methods to translate the vast amount of visual data generated in such experiments into quantitative variables describing platelet movements that can be subjected to systematic analysis. In this study, we developed experimental and computational protocols allowing for a detailed mathematical analysis of platelet movements within a developing thrombus. We used a flow chamber-based model of thrombosis wherein a collagen strip was used to initiate platelet adhesion and activation. Combining the use of a platelet staining protocol, designed to enable identification of individual platelets, and image processing, we tracked the movements of a large number of individual platelets during thrombus formation and consolidation. These data were then processed to generate aggregate measures describing the heterogeneous movements of platelets in different areas of the thrombus and at different time points. Applying this model and its potential, to a comparative analysis on a panel of platelet inhibitors, we found that total platelet intra-thrombus movements are only slightly reduced by blocking the interactions between glycoproteins IIb/IIIa and Ib and their ligands or by inhibiting thromboxane synthesis or P2Y12 signalling. In contrast, whereas 30 to 40% of the platelets movements (for the CD42a-labelled platelets) and 20% (for the pro-coagulant platelets), within a thrombus, are contractile, i.e., towards the centre of the thrombus, this contractile component is almost totally abolished in the presence of agents inhibiting these pathways.
Keywords: flow chambers; thrombosis; platelet aggregation; platelet contraction; fluorescence microscopy